نتائج طريقة الإرواء المستمر بالصادات الحيوية في سياق العلاج المركب لذات العظم والنقي المزمنة - جوني, أحمد (Latakia University Journal -Medical Sciences Series, 2014)
شملت الدراسة 84 مصاباً بذات العظم والنقي المزمنة (86 حالة) بأسباب مختلفة، وتوضع ودرجات مختلفة، وقد خضع جميع المرضى لعمل جراحي تمثل بتجريف واستئصال الأنسجة النخرية المنتنة، مع زرع نظام إرواء مستمر بالصادات وتمت متابعة الحالات لمدة سنة،وتم الحصول على نتائج إيجابية في 86% من الحالات، وكانت النتائج سلبية في 14% من الحالات. استطاعت طريقة الإرواء المستمر بالصادات الحيوية أن تؤمن وصولاً أكيداً للصادات الحيوية المختارة إلى بؤرة الإنتان بالتراكيز الكافية لقتل الجراثيم المسببة، مما سمح بالحصول على أفضل النتائج. Our study included (84) patients: 86 cases suffering from chronic osteomyelitis: various causes, location and degrees. All patients operated: after curettage of necrotic and infected tissues; system of continuous irrigation with antibiotics was inserted to the infected zone; all cases were followed up for 1 year. 86% of positive results were obtained and results were bad in 14% of cases> The high positive results (86%) confirm high effect of continuous irrigation with antibiotics as a good method for chronic osteomyelitis treatment, because this method allows delivery of suitable antibiotics in high concentration into the infected area, which is enough to kill microbes and allows to obtain best results.